A new Capsicum baccatum accession shows tolerance to wild‐type and resistance‐breaking isolates of Tomato spotted wilt virus. (16th June 2015) - Soler, S.; Debreczeni, D.E.; Vidal, E.; Aramburu, J.; López, C.; Galipienso, L.; Rubio, L.
Abstract Tomato spotted wilt virus (TSWV) causes economically important losses in many crops, worldwide. In pepper (Capsicum annuum), the best method for disease control has been breeding resistant cultivars by introgression of gene Tsw from Capsicum chinense. However, this resistance has two drawbacks: (a) it is not efficient if plants are infected at early growth stages and under prolonged high temperatures, and (b) it is rapidly overcome by TSWV evolution. In this work, we selected and evaluated a new accession from Capsicum baccatum, named PIM26‐1, using a novel approach consisting in measuring how three parameters related to virus infection changed over time, in comparison to a susceptible pepper variety (Negral) and a resistant (with Tsw) accession (PI‐159236): (a) The level of resistance to virus accumulation was estimated as an opposite to absolute fitness, W=er, being r the viral multiplication rate calculated by quantitative RT‐PCR; (b); the level of resistance to virus infection was estimated as the Kaplan–Meier survival time for no infection using DAS‐ELISA to identify TSWV‐infected plants; (c) the level of tolerance was estimated as the Kaplan–Meier survival time for no appearance of severe symptoms. Our results showed that the levels of both resistance parameters against TSWV wild type (WT) and Tsw‐resistance breaking (TBR) isolates were higher in PIM26‐1 than in the susceptible pepper variety Negral and similar to the resistant variety PI‐159236 against the TBR isolate. However, PIM26‐1 showed a very high tolerance (none of the plants developed severe symptoms) to the WT and TBR isolates in contrast to Negral for WT and TBR or PI‐159236 for TBR (most TSWV‐inoculated plants developed severe symptoms). All this indicate that the new accession PIM26‐1 is a good candidate for breeding programmes to avoid damages caused by TSWV TBR isolates in pepper.